DEVELOPING MATERIALS FOR TEACHING DESCRIPTIVE TEXTS THROUGH FACEBOOK FOR YEAR SEVEN STUDENTS OF JUNIOR HIGH SCHOOL - Prihatiningsih, Agustina (English Education Journal, 2011)
With the boom in technology and the popularization of Facebook amongschool students, many teachers and students are now utilizing this informationsharing network opportunity for academic purposes. In line with the newestcurriculum, School Based Curriculum (KTSP), which allow schools to developthe curriculum, this Research and Development (R&D) has inspired me indeveloping descriptive text material through Facebook. The material ispreferred for its importance to be taught in Year Seven Junior High School. Inthe process of developing the material, this study addresses three problems: (1)What is the initial condition of students before using the descriptive textsmaterial developed through facebook? (2) How is the material in facebookdeveloped for teaching descriptive text? (3) What is the influence of using thedescriptive texts material developed through facebook to the studentsachievement on writing competence?The scope of the study is developing material through facebook for teachingdescriptive text for Year Seven students of Junior High School so that they areable to create a simple short descriptive text or modify the text by using theirexperiences.In developing the descriptive text material through facebook, the method,Research and Development (R & D) was adapted and simplified from thedevelopment stages of Borg and Gall. The process started from doing a survey.Then, it was followed by developing material through facebook, experts andteachers validation, doing first revision, trying out the material, doing secondrevision, and ended by producing the final product. The developed product isthe material of descriptive text through facebook entitled "Lets describe it"addressed on letsdecribeit.co.ee. Whereas the content of the developed materialwas language features, generic structures, sentence based writing and genrebased writing.The real time in trying out the material was 270 minutes (excluding studentsfinal writing). As indicated by the students final writing and the teachersopinion in questionnaires, also the result of the study, the material in "Letsdescribe it" facebook is appropiate for teaching descriptive text for Year Sevenstudents of Junior High School. Hopefully, teachers are able to develop the